Subcutaneous infliximab in Crohn's disease patients with previous immunogenic failure of intravenous infliximab - Husman, Julia; Černá, Karin; Matthes, Katja; Gilger, Maximilian; Arsova, Maia; Schmidt, Alexandra; Winzer, Nadia; Brosch, Anna-Magdalena; Brinkmann, Franz; Hampe, Jochen; Zeissig, Sebastian; Lukáš, Milan; et al. (International journal of colorectal disease, 2024)
PURPOSE: Immunogenicity is a major reason for secondary loss of response to infliximab (IFX). Recent work suggested potentially lower immunogenicity of subcutaneous (SC) compared to intravenous (IV) IFX. However, it is unknown whether re-exposure to IFX SC after secondary loss of response and immunogenicity to its intravenous formulation is safe and effective. METHODS: In a retrospective cohort study conducted at two medical centers, patients with clinically (Harvey-Bradshaw Index ≥ 5) and/or biochemically (fecal calprotectin > 250 µg/g) active Crohn's disease (CD) and previous immunogenic failure of IFX IV underwent exposure to IFX SC. Harvey-Bradshaw Index, fecal calprotectin, IFX serum concentration, and anti-drug antibodies were assessed until month 12. RESULTS: Twenty CD patients were included. The majority of patients (90%) had previous treatment with three or more biologics. Fifteen (75%) and ten (50%) of 20 patients continued IFX SC treatment until months 6 and 12, respectively. No immediate hypersensitivity reactions were observed. Two patients discontinued IFX SC treatment because of delayed hypersensitivity at week 2 and week 4. IFX serum concentrations increased from baseline to month 12, while anti-drug antibody levels decreased. Combined clinical and biochemical remission at month 12 was observed in seven of 20 patients (35%). CONCLUSION: Subcutaneous infliximab treatment of Crohn's disease patients with previous immunogenic failure of intravenous infliximab was well tolerated and effective in a cohort of patients with refractory Crohn's disease.
Keywords: dospělí; infliximab; Infliximab; Female; feces; Feces; Administration, Intravenous; Subcutaneous infliximab; Refractory Crohn’s disease; Adult; mladý dospělý; ženské pohlaví; intravenózní podání; lidé; injekce subkutánní; Treatment Failure; leukocytární L1-antigenní komplex; CT-P13; retrospektivní studie; Crohn Disease; Male; Immunogenic failure; Injections, Subcutaneous; neúspěšná terapie; Young Adult; lidé středního věku; Crohnova nemoc; mužské pohlaví; Leukocyte L1 Antigen Complex; Retrospective Studies; Middle Aged; Humans